Clinical evidence of hyperbaric oxygen therapy for Alzheimer’s disease: a systematic review and meta-analysis of randomized controlled trials - Lin, Guangyao; Zhao, Li; Lin, Jingyu; Li, Xuanling; Xu, Lianwei (Frontiers in Aging Neuroscience, 2024)
Objective: To evaluate the potential benefits of hyperbaric oxygen intervention on people with Alzheimer's disease (AD) based on the existing randomized controlled trials (RCTs).: A systematic search was conducted in nine databases until November 17, 2023, for RCTs assessing the effect of hyperbaric oxygen intervention for AD. The primary outcomes included Mini-Mental State Examination (MMSE), Alzheimer's Disease Assessment Scale-Cognitive (ADAS-Cog), activities of daily living (ADL), and adverse events. All results were shown in forest plots, and sensitivity analysis was adopted to further verify the robustness of the pooled results. Results: A total of 11 RCTs recruiting 847 participants were included in this meta-analysis. Based on the pooled evidence, hyperbaric oxygen could remarkably ameliorate MMSE (MD = 3.08, 95%CI [2.56, 3.61], p < 0.00001), ADAS-Cog (MD = -4.53, 95%CI [-5.05, -4.00], p < 0.00001), ADL (MD = 10.12, 95%CI [4.46, 15.79], p = 0.0005), MDA levels (SMD = -2.83, 95%CI [-5.27, -0.38], p = 0.02), SOD levels (SMD = 2.12, 95%CI [1.10, 3.15], p < 0.0001), IL-1-β levels (SMD = -1.00, 95%CI[-1.48, -0.53], p < 0.0001), and TGF-β1 levels (MD = 4.87, 95%CI [3.98, 5.76], p < 0.00001) without adverse events (OR = 1.17, 95%CI [0.68, 2.03], p = 0.58) for people with AD. The pooled results were robust after checking by sensitivity analysis.Conclusions: These evidences suggest that hyperbaric oxygen is an effective and safe intervention for the treatment of AD. Further studies with more rigorous design will help to fully evaluate the clinical value of hyperbaric oxygen on cognition function in people with AD.